Modality Switching in Landmark-Based Wayfinding - Schwarz, Mira; Hamburger, Kai (Frontiers in Psychology, 2022)
This study investigates switching costs in landmark-based wayfinding using olfactory and visual landmark information. It has already been demonstrated that there seem to be no switching costs, in terms of correct route decisions, when switching between acoustically and visually presented landmarks. Olfaction, on the other hand, is not extensively focused on in landmark-based wayfinding thus far, especially with respect to modality switching. The goal of this work is to empirically test and compare visual and olfactory landmark information with regard to their suitability for wayfinding including a modality switch. To investigate this, an experiment within a virtual environment was conducted in which participants were walked along a virtual route of twelve intersections. At each intersection, landmark information together with directional information was presented, which was to be memorized and recalled in the following phase, either in the same or in the other modality (i.e. visual or olfactory). The results of the study show that, in contrast to the no-switching costs between auditory and visual landmarks in previous studies, switching costs occur when switching modality from visual to olfactory and vice versa. This is indicated by both longer decision times and fewer correct decisions. This means that a modality switch involving olfactory landmark information is possible but could lead to poorer performance. Therefore, olfaction may still be valuable for landmark-based-wayfinding. We argue that the poorer performance in the switching-condition is possibly due to higher cognitive load and the separate initial processing of odors and images in different cognitive systems.